Improvement of thermal ageing and transparency of methacrylate based poly(siloxane–silsesquioxane) for optoelectronic application. Issue 37 (6th June 2017) - Loh, T. C.; Ng, C. M.; Kumar, R. N.; Ismail, H.; Ahmad, Z.
ABSTRACT: Trisilanolphenyl–polyhedral oligosilsesquioxane (trisilanolphenyl–POSS) structure is introduced into a polysiloxane network in an attempt to produce thermally stable material with improved transparency. A series of organic–inorganic resins comprised of diphenylsilanediol, 3‐methacryloxypropyl trimethoxysilane, and varying content of trisilanolphenyl–POSS were copolymerized through condensation followed by curing using phenyltris(hydrogendimethylsiloxy)silane as curing agent. Fourier transform infrared spectroscopy (FTIR), proton‐nuclear magnetic resonance spectroscopy ( 1 H‐NMR), and silicon‐nuclear magnetic resonance spectroscopy ( 29 Si‐NMR) were used to confirm the synthesized product. Excellent thermal stability, improved glass transition temperature ( Tg ), and lower coefficient of thermal expansion with the increasing POSS content were observed from thermomechanical analysis. Its extreme thermal degradation stability was attributable to the crosslinked network as well as the heavily substituted aromatic ring present in the system. Steric hindrance effect is noticeable beyond 5.66 mol % trisilanolphenyl–POSS content. Incorporation of POSS substituent in methacrylate‐based polysiloxane give excellent transparency and improved thermal discoloration resistance as deduced from UV/vis Spectrophotometer, making it a potential material to be used in optoelectronics. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45285. Abstract :